CircRNA AFF4 induced by KDM1A promotes osteogenic differentiation through FNDC5/Irisin pathway - Ansong Liu; Yong Chen; Da Zhong; Chenggong Wang; Mi Yu; Chao Liu; Zhijun Yang; Wenkang Chen; Ke Yin (Molecular Medicine, 2022)
Abstract Background Circular RNA (circ) AFF4 was documented to regulate osteogenesis but the underlying mechanism remains to be elucidated. The preliminary study showed that circ_AFF4 may promote osteogenesis via FNDC5/Irisin. Furthermore, the online prediction tool indicated the interaction of circ_AFF4, insulin-like growth factor-2 mRNA-binding protein 3 (IGF2BP3), FNDC5 and lysine (K)-specific demethylase 1 A (KDM1A). Therefore, this study aims to elucidate the relationships of KDM1A, circ_AFF4, IGF2BP3 and FNDC5/Irisin during osteogenesis. Methods The alkaline phosphatase (ALP) activities and osteogenic-related factors were determined using ALP and alizarin red S (ARS) staining, real-time quantitative PCR(RT-qPCR) and western blot. Immunoprecipitation (RIP), pull-down assay and fluorescence in situ hybridization (FISH) were used to examine the interactions among circ_AFF4/IGF2BP3/FNDC5. A mouse in vivo model was utilized to further confirm the regulatory effect on bone formation. Results Circ_AFF4 and KDM1A expression levels were increased during osteoinduction of BM-MSCs. Knockdown of circ_AFF4 and KDM1A significantly suppressed BM-MSC osteogenesis. We also proved that KDM1A directly bound to circ_AFF4 and FNDC5 promoter and induced circ_AFF4 and FNDC5 expression. Furthermore, circ_AFF4 enhanced the stability of FNDC5 by generating a circ_AFF4, IGF2BP3 and FNDC5 RNA-protein complex, and thereby induced Irisin and osteogenesis. The in vitro data was confirmed with in vivo model. Conclusion These findings elucidate that KDM1A induces circ_AFF4, which promotes promote osteogenesis via IGF2BP3. This study indicates that circ_AFF4 may potentially represent a critical therapeutic target for the diseases.